Environmental Kuznets Curve for the Informal Sector of Turkey (1950-2009) - Elgin, Ceyhun; Öztunalı, Oğuz (Panoeconomicus, 2014)
In this study we investigate the empirical relationship between the size of the informal sector (as percentage of official GDP), carbon dioxide and sulfur dioxide emissions in Turkey by using annual data from 1950 to 2009 and conducting a time-series analysis using cointegration techniques. This analysis is crucial as pollution emissions may lead to unfavorable weather conditions and potentially cause environmental impacts that may adversely affect the global economy. The empirical analysis shows evidence towards the existence of an inverted-U relationship between relative informal sector size and environmental pollution indicators in the long-run. That is small and large sizes of the shadow economy are associated with little environmental pollution and medium levels of the size of the shadow economy are associated with higher levels of environmental pollution. Moreover, using multivariate cointegration techniques, we suggest and test an economic mechanism to account for this observation. This also helps us to prescribe various policy recommendations regarding pollution and energy use. Key words: Informal economy, Error correction model, Cointegration, Greenhouse gas, Turkish economy. JEL: E26, O17, Q53.